Nilai Sosial Dalam Novel Ayah Karya Andrea Hirata - Dewi, Ciptaning Tyas Kusuma (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis is aimed to know the social value on Novel Ayah written by Andrea Hirata (The Study of Dynamic structuralism). The method used is a qualitative descriptive method by describing social value analyzed by the content analysis technic of a novel Ayah written by Andrea Hirata. Social value is described according to dynamic structuralism approach . The social values among others ; the truth, moral and religious. The values in the quotation is attached to intrinsic elements in the theme, character, disposition, and background. The research can be concluded that social values in novel Ayah among others; the truth, moral, and religious. The velue frequency appears in novel Ayah is the truth velues. The most dominant of novel structure in the social values is the characteristic element. In education social values have the function as it containts social values connecting to dreamsor stimulus hope directing students how to think and act such as the guiding of deciding choice. The existence of literature can create interest, honest, emotional sensitivity and the knowledge of intelectual life for students. The social knowledge is expected to be able to help students in developing the knowledge and applying positive social value in life.